‘I’m no Medievalist’: George Gilbert Scott and the Interpretation of the Gothic Revival in Remarks on Secular and Domestic Architecture: Present and Future (1857) - Isabelle Cases (Cahiers Victoriens et Edouardiens)
In 1857, George Gilbert Scott gathered a number of writings and reflections in Remarks and presented himself as a staunch defender of Gothic in the then raging battle of styles. He nevertheless started controversies in the Gothic Revival movement by criticizing a strict imitation of the past and defending the use of Gothic for all sorts of buildings other than religious. This definition of a true Gothic Renaissance owed him harsh criticisms from famous medievalists, especially on the questions of restoration and the industrial society of his time, but also reveals contradictions and tensions within the Gothic Revival.